Effect of PM2.5 and PM10 on the Hematopoietic System of Cafés Workers in Baghdad - Abdul Bari Fezea, Mohammed; Gathwan, Maha A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The aim of our current study was to identify the effect of particulate matter of both types (PM2.5 and PM10) resulting from hookah smoking on the hemopoietic system of workers (smokers) in closed cafes. This study included six stations (cafes) on the Rusafa side of Baghdad city and conducted a blood test that included a complete blood count (CBC). A multifunctional air quality detector measured both types of particulate matter in the morning peak and evening peak. The study included 30 men (workers and smokers) and 30 men (non-smokers), whose ages ranged from 20 to 40 years. The study found that smokers had an increase in white blood cells and red blood cells, as well as an increase in the percentage of hemoglobin (HGB), hematocrit (HCT), the mean corpuscular volume (MCV), and the number of platelets (PLT), while also showing a decrease in the mean corpuscular hemoglobin concentration (MCHC). There was a significant difference between PM2.5 in the morning and hemoglobin, or platelets, in smokers. Additionally, smokers showed a significant difference between PM2.5 in the evening, PLT, and MCV. In the case of PM10, a significant difference was found between it and the blood platelets of smokers in the morning, while PM10 in the evening was found to have a significant difference with PLT and MCV among the smokers group.